2016
DOI: 10.1155/2016/7690697
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Postmigration Living Difficulties on the Mental Health of Afghan Migrants Residing in Istanbul

Abstract: Background. The sociopolitical situation in Afghanistan continually pushes Afghans to seek safety and better socioeconomic prospects in neighboring and foreign countries. In this paper we examine the mental health of Afghan migrants residing in Istanbul, Turkey, an understudied population at high risk of psychopathology. Methods. We surveyed 158 Afghan migrants to assess psychological distress using a culturally grounded measure of mental health, the Afghan Symptom Checklist [ASCL], and used hierarchical regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…Also, the narratives captured in this study, further emphasize other findings from our structured survey [18] highlighting the great frequency with which Afghans in Istanbul have experienced a variety of stressors and deprivations. These include poverty and unemployment, no access to medical care, fear of being returned to Afghanistan, loneliness, isolation, concerns about family back home, and significant exploitation by employers.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Also, the narratives captured in this study, further emphasize other findings from our structured survey [18] highlighting the great frequency with which Afghans in Istanbul have experienced a variety of stressors and deprivations. These include poverty and unemployment, no access to medical care, fear of being returned to Afghanistan, loneliness, isolation, concerns about family back home, and significant exploitation by employers.…”
Section: Discussionsupporting
confidence: 70%
“…countries, yet has no provisions for Afghans [17]. Our recent cross-sectional survey of Afghan migrants in Istanbul shows that exclusionary legal processes for claiming residency, without which one cannot be gainfully employed, may be the basis for the high rates of post-migration living difficulties (poverty, isolation, unemployment, fears of being sent home, asylum challenges) that negatively impact the health and well-being of Afghans [18]. And in a later study, we found that despite their poor mental and physical health status, the precarious conditions in which they live were a plausible reason for their low reported use of professional health services [19].…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that post-migration living difficulties are usually grouped in a few clusters, such as family issues, discrimination, asylum procedure, socioeconomic living conditions, socio-religious aspects, and work-related issues (Laban, Gernaat, Komproe, Van Der Tweel, & De Jong, 2005). Many studies indicated a negative impact that these stressors have on refugees' physical and mental health (Alemi et al, 2016;Hallas, Hansen, Staehr, Munk-Andersen, & Jorgensen, 2007;Laban, Komproe, Gernaat, & de Jong, 2008;Li, Liddell, & Nickerson, 2016;Schweitzer, Melville, Steel, & Lacherez, 2006;Steel, Silove, Bird, & McGorry, 1999).…”
Section: Pre-migration and Post-migration Factorsmentioning
confidence: 99%
“…Lack of healthcare at this age may expose women to pregnancy and obstetric complications after birth. Several studies among Afghans, Somalis, Iraqis and Syrian refugees suggest that women face physical and mental health challenges (Alemi et al, 2016;Bogic et al, 2015;Gerritsen et al, 2006;Ghumman et al, 2016;Hassan et al, 2016;Lillee et al, 2015;Maximova & Krahn, 2010;Taylor et al, 2014). A study by Hassan et al (2016) suggested that Syrian women experienced a wide range of mental health problems because of the war and immigration.…”
Section: Introductionmentioning
confidence: 99%